A Study on Lump and Interaction Solutions to a (3 + 1)-Dimensional Soliton Equation. (16th October 2019) - Liu, Xi-zhong; Lou, Zhi-Mei; Qian, Xian-Min; Thiam, Lamine
Abstract : Based on bilinear formulation of a (3 + 1)-dimensional soliton equation, lump solution and related interaction solutions are investigated. The lump solutions of the soliton equation are classified into three cases with nonsingularity conditions being given. The interaction solutions between lump and a stripe soliton are obtained in eight cases, which have interesting fusing and fission behaviors with changing time. The interaction solutions of the soliton equation between a lump and a resonant pair of stripe solitons are also given, and we find that the lump just exist for a finite period during the interaction process.